Genetic variation of agarwood producing tree (Gyrinops versteegii) from Pongkor, Manggarai District, Flores Island, Indonesia using ISSR molecular markers - ALFI FAUZAN IRSYAD; Ridesti Rindyastuti; TITUT YULISTYARINI; AGUNG SRI DARMAYANTI; BUDI SETIADI DARYONO (Society for Indonesian Biodiversity, 2020)
Abstract. Irsyad AF, Rindyaastuti R, Yulistyarini T, Darmayanti AS, Daryono BS. 2020. Genetic variation of agarwood producing tree (Gyrinops versteegii) from Pongkor, Manggarai District, Flores Island, Indonesia using ISSR molecular markers. Biodiversitas 21: xxxx. Agarwood is a black-colored tree wood that produces distinctive sap because of fungal infections which belong to Thymelaeaceae family (mainly Aquilaria and Gyrinops). Agarwood product is highly valuable that leading to over exploitations by the collectors. To develop the most effective and efficient conservation strategies, genetic information from these plants is required. The aims of this research are to determine the genetic variation and to confirm the species identity of agarwood producing tree (Gyrinops versteegii (Gilg.) Domke) population in Pongkor Community Forest, Pongkor, Manggarai District, Flores Island, East Nusa Tenggara. Information of the genetic variation, as well as the phenetic relatedness, were evaluated with inter-simple sequence repeat molecular marker (ISSR) using five primers; Ng2.01, Ng2.06, Ng3.01, Ng3.02, and UBC 855, with two other agarwood producing species as outgroup (Aquilaria filaria and Gyrinops decipiens). Amplified bands from all primers showed 55.17% polymorphic bands in G. versteegii. Genetic variation of G. versteegii identified with Nei’s genetic diversity (h value) obtained at 0.218. Clustering analysis from UPGMA dendrograms formed three major clusters. Degree of similarity of G. versteegii based on the dendrograms obtained at 85.9% using SSM method. The results showed close phenetic relatedness between individuals and relatively high genetic variation of G. versteegii, however, imply the need for strictly maintenance of habitat preservation and larger population size.